Remembering Nepal Earthquake of 2015 and Updating Post-earthquake Reconstruction - Dangal , Ganesh; Dangal, Ojash; Gelal, Dharana (Europasian Journal of Medical Sciences, 2021)
Nepal earthquake of 2015, a massive earthquake that struck near the city of Kathmandu (Gorkha) in central Nepal on April 25, 2015. Nearly 9,000 people were killed, many thousands more were injured, and more than 600,000 structures in Kathmandu and other nearby 31 districts were either damaged or destroyed. The earthquake was felt throughout central and eastern Nepal, much of the Ganges River plain in northern India, and northwestern Bangladesh, as well as in the southern parts of the Plateau of Tibet and western Bhutan. DOI: https://doi.org/10.46405/ejms.v3i2.352